Evaluation of the Diagnostic Performance of Physical Examination Combined with Transvaginal Ultrasonography in Patients with Endometriosis - Talha Tiryaki; Tolga Karacan; Seyma Yesiralioglu; Eser Ozyurek; Huseyin Kiyak; Engin Oral (Gynecology Obstetrics & Reproductive Medicine)
Objective: Owing to its high sensitivity and specificity, and because it is widely available, transvaginal ultrasonography is the first-line imaging test of choice used for the diagnosis of endometriosis. Ultrasonographic findings evaluated in conjunction with symptoms and signs may improve the diagnosis of endometriosis. Therefore, we hypothesized that transvaginal ultrasonography combined with physical examinations performed by physicians could predict endometriosis better in patients with symptoms suggestive of endometriosis compared with asymptomatic patients at presentation.